A comparison of personality indicators across three cultural groups - Meyer Ginsberg, Aniela (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The Holtzman Inkblot Test (H IT) was administered to 18 6 male university students grouped in these ways: Brazilians, fourth generation or more; Nisseis, first generation Brazilians of Japanese descent; and Japanese, studying in Tokyo. The groups were further divided according to the educational level of the father of each subject. Subject scores on 33 variables from the HIT were reduced by means of analyses of variance according to ethnic origin and father's education. The numerous statistically significant differences suggested that the HIT variables differentiate between ethnic groups in the following general ways: with respect to precision and integration of perceptions, creative fantasy, anxiety, oppositional and dysphoric affective attitudes, social adaptability, and special interests.